2016
DOI: 10.1002/qua.25155
|View full text |Cite
|
Sign up to set email alerts
|

About the difference between density functionals defined by energy criterion and density functionals defined by density criterion: Exchange functionals

Abstract: The difference between density functionals defined by energy criterion and density functionals defined by density criterion is studied for the exchange functional. It is shown that Slater potentials are exact exchange potentials in the sense that they yield the Hartree-Fock electron density if all operators are given by local expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For groundstate systems the formal exact expression for the Pauli potential vP(truer) has been derived in Refs. [15 and ] and the Slater potential has been shown to be the corresponding local potential yielding the HF electron density, when the kinetic energy is equally expressed as a local operator (as it is the case in an orbital‐free ansatz according to Equation ). The strategy for deriving Equations is the same as the strategy that has been used by Staroverov and his colleagues to derive the exact KS exchange potential and the exact KS exchange‐correlation potential associated with a specified electron density …”
Section: Theorymentioning
confidence: 99%
“…For groundstate systems the formal exact expression for the Pauli potential vP(truer) has been derived in Refs. [15 and ] and the Slater potential has been shown to be the corresponding local potential yielding the HF electron density, when the kinetic energy is equally expressed as a local operator (as it is the case in an orbital‐free ansatz according to Equation ). The strategy for deriving Equations is the same as the strategy that has been used by Staroverov and his colleagues to derive the exact KS exchange potential and the exact KS exchange‐correlation potential associated with a specified electron density …”
Section: Theorymentioning
confidence: 99%
“…It has been shown recently that the exact exchange potential yielding the HF electron density from a purely local density functional formalism (not a Kohn–Sham formalism) is the Slater potential: vS([n];truer)=12n(truer)|γfalse(r,rfalse)|2|rr| dtruer , where the first order reduced density matrix γ(truer,truer) is given by: γ(truer,truer)=ioccϕi*(truer)ϕi(truer) and the sum runs over all occupied HF orbitals ϕi(truer). Therefore, the Euler equation yielding the HF electron density as minimizing density from a local density functional formalism can be written as: 0=vW([n];truer)+vext([n];truer…”
Section: Theorymentioning
confidence: 99%
“…Recently, it has been shown that the Slater potential numerically corresponds to the exact exchange potential yielding the Hartree–Fock electron density from Hohenberg–Kohn principle when the kinetic energy is equally expressed by a local operator, as for example realized in orbital‐free calculations . This approach for the exact exchange potential must be distinguished from the optimized effective potential method and the method of obtaining Kohn–Sham wavefunctions and potentials from given constraint density in which case the kinetic energy operator is nonlocal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations